Seroprevalence of Helicobacter Pylori Infection among Patients with Gastroduodenal Disorders in Erbil City - D Majeed, Pshtewan; Jwan Saleh Khoshnaw, Karim (Diyala Journal of Medicine, 2020)
Background: More than half of the world's population is influenced by Helicobacter pylori infection. The infection is commonly obtained during childhood but may stay asymptomatic, with long-term clinical consequences such as gastritis, peptic ulcer illness, and stomach cancer. Objective: To determine the prevalence rate of Helicobacter pylori infection and related variables such as age, gender, residency, blood group, Rhesus factors and previous infection among patients presenting with gastroduodenal disorders in Erbil city. Patients and Methods: Out of 240 blood samples from patients with gastroduodenal disorders admitted to Rzgary Teaching Hospital in Erbil, Iraq from July to August 2019 were collected and screened for anti-Helicobacter pylori antibodies by rapid immunochromatographic assay, and blood groups of patients were determined by using hemagglutination test. For each study subject, a questionnaire sheet was prepared and used. Results: The overall prevalence rate of Helicobacter pylori infection among 240 patients with gastroduodenal disorders was 128 (53.3%). A significant relationship between Helicobacter pylori infection and gender (male 43.75% and female 59.72%) was recorded (P<0.05). The highest rate of Helicobacter pylori infection was founded among the age group over 50 years, but there were no significant differences between them (P>0.05). Prevalence was significantly higher among rural areas (60.4%) than the urban areas (48.6%) (P<0.05). There was a significant association between Helicobacter pylori infection and ABO blood group phenotypes (P<0.05), but there is no significant association between Helicobacter pylori infection and the type of Rhesus factor (P>0.05). Prevalence was significantly higher among the previous infection (78.5%) than non-previous infection (23.6%) (P<0.05). Conclusion: We found that in Erbil city, the seropositivity of anti-Helicobacter pylori antibody was high among patients with the gastroduodenal disorder. The high prevalence of Helicobacter pylori was founded in the women, elderly, rural area, O blood group, positive Rhesus factor and patients with the previous infection.